Relación entre el empleo y la afiliación al fondo de pensiones en Loreto en el periodo 2019 – 2023 - Felix Camiñas, Monica Elvira (2024)
The pension fund is a system that manages the contributions of workers throughout their working life, to ensure a regular income during retirement and maintain a decent standard of living, covering basic needs. In this sense, our research analyzes the relationship between formal employment and membership in the pension fund in Loreto in the period 2019-2023. In the development of the research, a quantitative approach was chosen, at a correlational level and a non-experimental design, with the study population being the total EAP of Loreto in the years 2019-2024. The results reveal that unemployment went from 32.84% in 2019 to 31.09% in 2023, being almost invariant. Likewise, formal employment went from 21.04% in 2019 to 16.61% in 2023 and pension fund membership went from 22.87% in 2019 to 19.97% in 2023. Finally, the Spearman's Rho = 0.585 and the bilateral Sig. = 0.000 were identified; concluding that there is a high positive relationship between formal employment and pension fund membership in Loreto in the period 2019-2023. Therefore, as formal employment increases in Loreto, so does pension fund membership